(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2017)
Background: The decision to use a contraceptive and the choice of method of contraception is partly informed by its effects on the health of users. The impact of a contraceptive on the incidence of cancer may be regarded as of greatest significance. Objective: To present a review of literature on the association between cancer and use of Oral Contraceptives (OCs), Depot Medroxyprogesterone Acetate (DMPA)and Intrauterine Contraceptive Devices (IUDs). Methods: This was a narrative review in which studies were identified through a search of the CINAHL, MEDLINE and EMBASE databases. Included are studies assessing the association between cancer and OCs, DMPA or IUDs published in English up to March, 2017. Overall, 27 studies were selected: 16 examined association with use of OCs, eight assessed association with IUDs and eight with DMPA. Data from the selected studies were extracted as reported in the studies. Results: Oral Contraceptives (OCs) are associated with a slight or no increase in the risk of breast cancer: 49 instead of 44 per 10,000 women, confined to use within the last 10 years. However, OCs do not alter the risk of mortality from breast cancer. Use of OCs for ≥5 years in the presence of HPV infection may increase the risk of and mortality from cervical cancer. OCs are inversely associated with endometrial, colorectal and ovarian cancer (50%, 20-30%, and 30-40% lower risk for ever- compared to never-use, respectively). Overall, there was a decrease in the incidence of cancer by 10 to 45 per 100,000 women per year in OCs users. The association between DMPA and breast cancer may be similar to that of OCs use. Overall, a higher risk of cancer (7% increase in incidence) has been reported in levonorgestrel-releasing IUDs users. Conclusion: Use of OCs is associated with a lower risk of cancer. The association between cancer and use of contraceptives other than OCs merits further assessment.